Reliability and validity of the Chinese version of the self-directed learning instrument in Chinese nursing students - Ziyun Gao; Lin Zhang; Jianing Ma; Hong Sun; Mengya Hu; Meiding Wang; Haiyang Liu; Leilei Guo (BMC Nursing, 2023)
Abstract Background In a rapidly changing healthcare environment, Self-directed learning (SDL) ability is recognized as a crucial condition for nursing students and nurse to deal with severe challenges positively. Developing SDL ability is becoming more and more important among nursing students. SDL is related to nursing students enhancing their own knowledge, skills and maintaining lifelong learning. This study is aim at translating the Self-directed Learning Instrument (SDLI) into Chinese and verify its reliability and validity among nursing students. Methods The study adopted a cross-sectional design and the multistage sampling design. The SDLI was translated into Chinese, and the reliability and validity of the scale were tested among 975 nursing students. Results The Cronbach’s α value of the Chinese version of SDLI was 0.916. The split-half reliability coefficient was 0.829, and the retest coefficient was 0.884. The content validity index of the scale was 0.95. Furthermore, the four-factors model was obtained by using exploratory factor analysis, explaining 55.418% variance, and the communalities of the items ranged from 0.401 to 0.664. With modified confirmatory factor analysis, the fit indices were chi-square/degree of freedom (CMIN/DF) = 2.285, the comparative fit index (CFI) = 0.947, and the tucker lewis index (TLI) was 0.938. And, the model fitting indexes were all in the acceptable range and confirmatory factor analysis indicated that the model fit the SDLI well. Conclusion The Chinese version of SDLI has good validity and reliability among nursing students. It can be used to measure the SDL ability of nursing students in China.